Teacher effectiveness and teacher growth from student ratings: An action research of school-based teacher evaluation. (September 2021) - Chen, Huijuan; Li, Mingyao; Ni, Xinyu; Zheng, Qiao; Li, Lingyan
Highlights: We build an action research framework for school-based teacher effectiveness evaluations. School-based instruments for student ratings of teacher effectiveness have valid statistical properties. Teacher effectiveness presents changing trajectories for different subgroups. The majority of teachers were positive about this evaluation through the meta-evaluation. Abstract: Teacher effectiveness evaluations are considered an effective mechanism for promoting teacher growth. We implemented teacher effectiveness evaluations in three Chinese secondary schools over two years and (a) developed an action research framework for school-based teacher evaluations composed of five links, i.e., purpose and consensus, data collection and analysis, data interpretation and feedback, data use, and evaluation of the actions and (b) found that "school-based" instruments of student ratings have valid statistical properties, and teacher effectiveness can be regarded as a single-factor holistic concept in different schools. We also (c) analysed 2-year longitudinal data and identified changing trajectories of teacher effectiveness as an example for data feedback and use. Teacher effectiveness presents changing trajectories for different subgroups, representing different ecologies in three schools and provides insights for teacher growth. A (d) meta-evaluation of the actions shows that most teachers are positive about this evaluation, although differences are observed between schools.